Evaluating the propensity for entrepreneurship among university students - Couto, João Pedro Almeida (2018)
Entrepreneurship is a major element in fostering the dynamics of an economy and bringing new types of competitive business. The value of this new business depends a lot on the capabilities of the entrepreneurs. Having a university degree is a relevant aspect to the establishment of high value added new ventures that capture knowledge and innovative technologies. Thus the purpose of this paper is to understand the propensity to entrepreneurship among university students and the factors that influence this propensity. Therefore we contribute to the literature on entrepreneurship by analysing the factors that determine the propensity for starting a new business among a specific segment of individuals that due to their education can foster the creation of high value ventures and positively influence the economic development of an economy. We use a sample of university students in Portugal to test a framework of variables that tries to weight the influence of socio-demographic variables, psychological characteristics and contextual factors, namely the type of universities and course and national institutional framework, applying a probabilistic model to test the relative importance of these factors. The results show nationality, gender, enrolment in academic associations and family background are the more significant factors that differentiate students that consider starting a new business. Other relevant elements are the level of income, sports activity engagement and travelling abroad experience.